2019
DOI: 10.3389/fphar.2018.01517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium-Glucose Co-transporter 2 Inhibitors on Bone Metabolism and Fracture Risk

Abstract: The effect of anti-diabetic medications on bone metabolism has received increasing attention, considering that type 2 diabetes mellitus is a common metabolic disorder with adverse effects on bone metabolism. Sodium-glucose co-transporter 2 (SGLT2) inhibitors are novel anti-diabetic medications that prevent glucose resorption at the proximal convoluted tubules in the kidney, increasing urinary glucose excretion, and decreasing the blood glucose level. The superiority of SGLT2 inhibitors shows in reducing the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 75 publications
0
38
0
1
Order By: Relevance
“…20 Animal experiments also showed that canagliflozin can increase the concentration of phosphate, FGF23, and PTH, whereas tofogliflozin has been shown to have no clear effect on bone mass by microcomputed tomography. 38 Whether the difference in selectivity for SGLT-2/ SGLT-1 and different bone biomarkers lead canagliflozin to have a higher fracture incidence remains uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…20 Animal experiments also showed that canagliflozin can increase the concentration of phosphate, FGF23, and PTH, whereas tofogliflozin has been shown to have no clear effect on bone mass by microcomputed tomography. 38 Whether the difference in selectivity for SGLT-2/ SGLT-1 and different bone biomarkers lead canagliflozin to have a higher fracture incidence remains uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms to explain possible SGLT2 inhibitor-associated effects on bone metabolism have been proposed. 33 Type 2 diabetes mellitus adversely effects bone metabolism and strength and increases the risk of fracture in affected individuals. 34…”
Section: Bone Fracturesmentioning
confidence: 99%
“…16 The relationship between SGLT-2 inhibitors and bone fracture has been described as unclear, and further study is expected. 23 More detailed information regarding DDIs with the coadministration of ART and T2DM medications can be found in the Liverpool HIV prescribing resources. 16…”
Section: Managing T2dm In the Presence Of Artmentioning
confidence: 99%